Use of Portfolio in Linguistics and Its Influence on Attitude and Understanding of Students at IPB Internasional - Putu Dian Yuliani Paramita (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This ponders points to display the utilize of Portfolios to create students' self-learning and understanding: shapes, employments, and comes about. Portfolios can increment students' understanding of addresses and cultivate understudy obligation in completing a specific work. Analysts utilized a subjective approach through perception, surveys, and documentation. The comes about of this ponder demonstrate that learning with portfolios within the shape of rundowns and concept maps is at that point displayed in two dialects, to be specific English and Indonesian inside ten minutes for each dialect. By employing a portfolio, understudies are not as it were free and get it in learning, but too hone dialect aptitudes